PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSE BUYING PRODUK FASHION PADA KONSUMEN SHOPEE DI LAMPUNG: PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSE BUYING PRODUK FASHION PADA KONSUMEN SHOPEE DI LAMPUNG - Syifa Nur Fadhillah; Arseta Lesmana; Syara Purnama Sari; Rahmawati Azizah (Sekolah Tinggi Ilmu Ekonomi Al-Madani, 2025)
This research aims to test the effect of electronic word of mouth and hedonic shopping motivation on impulse buying of fashion products by Shopee consumers in Lampung. The type of research used is quantitative research with an associative approach method. The data used are primary data, the source of data obtained comes from the results of the questionnaire. The sample in this study were Lampung people who used the Shopee application and had done impulse buying. Data collection was carried out with a questionnaire distributed to 140 people. The statistical method used Multiple Linear Regression Analysis, with hypothesis testing of the t-statistic test. The results of this study indicate that electronic word of mouth and hedonic shopping motivation have a significant effect on impulse buying.